2011
DOI: 10.1167/iovs.11-7260
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Rate of Myopia Progression with a Contact Lens Designed to Reduce Relative Peripheral Hyperopia: One-Year Results

Abstract: The 12-month data support the hypothesis that reducing peripheral hyperopia can alter central refractive development and reduce the rate of progress of myopia. (chictr.org number, chiCTR-TRC-00000029 or chiCTR-TRC-00000032.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
297
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(334 citation statements)
references
References 30 publications
11
297
2
2
Order By: Relevance
“…Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, alpha-ganglion cells are predominantly observed in the peripheral retina and have large dendritic regions to receive inputs from amacrine cells 47,[53][54][55][56][57] . The hypothesis that alpha- ganglion cells and AII amacrine cells are implicated in emmetropization is consistent with the peripheral defocus theory, a theory of myopia development that has been supported by clinical evidence [58][59][60][61] .…”
Section: Discussionsupporting
confidence: 74%
“…68 Similarly, the rate of progression of myopia was reduced by B30% in eyes wearing contact lenses designed to reduce hyperopic defocus compared with single-vision spectacles. 69 Also of interest, orthokeratology has also been found to be effective in reducing progression of myopia, and it has been suggested that the underlying mechanism involves reduction in peripheral hyperopic defocus. One 5 year study found an increase in axial length of 0.99±0.47 and 1.41±0.68 mm for orthokeratology groups and a control group of spectacle lens wearers and indicates a significant slowing of ocular growth with orthokeratology.…”
Section: Undercorrectionmentioning
confidence: 99%
“…(Mutti et al 2000a, Mutti et al 2007 Moreover, the differences in myopic progression in eyes with more RPH may be so small as to be clinically irrelevant -a 2010 study showed that each dioptre of RPH increased myopic progression by only 0.025D per year. (Mutti et al 2010) The presumption of relative peripheral hyperopia in myopes driving axial elongation has been repeatedly challenged in the literature (Sng et al2011, Lee and Cho 2013 yet is still the presumed mechanism of spectacle and soft contact lens (Anstice and Phillips 2011, Sankaridurg et al 2011, Lam et al 2014 designs examined to reduce axial elongation in myopes, and also of OK's similar efficacy, , Walline 2016 -no link between RPH changes and reduction in axial elongation in any of these designs, including OK, has been proven experimentally.…”
Section: Peripheral Refraction and Myopiamentioning
confidence: 99%
“…The peripheral add multifocal designs included a commercially available distance-centred multifocal SCL, previously indicated for presbyopia; and three novel designs -a +0.50 Add with nasally decentred optics; (Fujikado et al 2014) a 'soft radial refractive gradient' lens purporting a +2.00 Add at the 35 0 retinal eccentricity and up to a +6.00 Add at the edge of the optic zone (8mm diameter); (Paune et al 2015) a lens with +1.00 Add at 4mm diameter increasing to +2.00 at the 9mm optic zone edge. (Sankaridurg et al 2011) This meta-analysis also included a lens with positive spherical aberration in the latter group, (Cheng et al 2016) which does not report any effect on RPH and is discussed below.…”
Section: (Shen Et Al 2010)mentioning
confidence: 99%
See 1 more Smart Citation